LEGAL DEVELOPMENT POLICY DIRECTION IN THE PERSPECTIVE OF SOCIAL JUSTICE - Fatkhul Muin (Fakultas Hukum Universitas Islam Syekh Yusuf, 2023)
This study focuses on legal development in various aspects of the life of the nation and state. The main dimension in legal development has a negative correlation and a positive correlation for the people. The perspective of authoritarian legal characteristics in legal development will encourage legal development that can damage the order of substantial justice in various aspects of people's lives, so that the law that is built must be based on the urgency of the interests of the community to achieve the ideals of the Indonesian nation as stated in the preamble of the 1945 Constitution of the Republic of Indonesia. The constitutional instrument clearly lays out the main fundamental values in aspects of the life of the nation and state, but in the process of implementing the constitution requires derivative norms that can provide further policy direction for the implementation of the constitution. From this perspective, the dimensions of the rule of law in legal development are illustrated with the aim of creating substantive social justice, not based on the interests of certain parties by placing variable interests in legal development for the welfare of society. This study aims to explore the perspective of legal development to achieve social justice with a legal approach. Keywords: Policy, Legal Development and Social Justice